DYNAMICS OF THE GROWTH-GENDER NEXUS IN INDONESIA: A CAUSALITY APPROACH AND MACROECONOMIC LAG EFFECTS ON THE GENDER DEVELOPMENT INDEX - Mhd. Arief Rizky (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the dynamics of the growth-gender nexus in Indonesia by examining the relationship between economic growth, macroeconomic indicators, and the Gender Development Index. This study uses a quantitative approach with annual time series data from Indonesia for the period 2010–2025. The dependent variable in this study is the Gender Development Index, while the independent variables include real GDP growth, inflation, the Open Unemployment Rate, and the poverty rate. The analysis method used is the Autoregressive Distributed Lag (ARDL), followed by diagnostic tests and Granger causality tests. The best model selected is ARDL (1,0,0,1,1). The estimation results show that GDP growth has a positive influence on the Gender Development Index, but it is not yet significant at the 5% level. Inflation, unemployment, and poverty also do not have a significant effect on the Gender Development Index. The Bounds Test results indicate that there is no long-term relationship between variables because the F-statistic value of 1.905563 is smaller than the lower bound value. Therefore, the model was not continued to the Error Correction Model. The Granger causality test also showed no causal relationship between GDP growth and the Gender Development Index. However, a one-way causality was found between the Gender Development Index and poverty. This finding suggests that Indonesia's economic growth has not automatically strengthened gender development. Gender development needs to be strengthened through more direct and specific policies, rather than relying solely on macroeconomic growth.